Pengujian Berbagai Varietas Padi (Oryza sativa L.) terhadap Kondisi Cekaman Fe2+ Di Lahan Pasang Surut: Pengujian Berbagai Varietas Padi (Oryza sativa L.) terhadap Kondisi Cekaman Fe2+ Di Lahan Pasang Surut - Karterine Dewi Endah Dirgasari; Mery Hasmeda; Umar Harun (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2019)
The developing plant cultivation at tidal land has constrained related to Fe2+ stressing which inhibits its growth and production. These study objectives are to identify growth characteristics and production capacity of some rice varieties as well as to find out the variety that tolerance to the Fe2+ stress at tidal land. The method of the study is Single Group Randomized Design with 20 varieties with three times of repetition. Advanced test with LSD 5%. Treatment with application 20 rice varieties, namely; Towuti, Siam Unus, Mashuri, Mekongga, Ciherang, Cilamaya Muncul, Pokalli, IR 64, Siak Raya, Inpari 30, Inpara 1, Limboto, Inpara 3, Inpara 4, Inpara 5, Inpara 6, Inpara 7, Inpara 8, Inpara 9 dan Awan Kuning. The results of the study show that root length, number of sampling, the weight of grain per plot highly significant deference toward observed parameters. The Varieties Mashuri, Mekongga, Towuti, Siam Unus dan Awan Kuning were the response to hight tolerance Fe2+ stress condition at tidal land.